Integrating Indigenous Knowledge through Contextual Project-Based Learning: Student–Healer Collaboration and Phytochemical Investigation of Traditional Ethnomedicine in Lombok, Indonesia - Faizul Bayani; Joni Rokhmat; Aliefman Hakim; AA Sukarso (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
This study investigates the implementation of a contextual Project-Based Learning model (Ethnomed-PjBL) that connects pharmacy students with traditional healers (Belian) in Lombok, Indonesia, to explore and scientifically validate ethnomedicinal formulations. Conducted in three phases field immersion, in-situ qualitative testing, and laboratory-based phytochemical analysis the model facilitated reciprocal learning and empirical inquiry grounded in Indigenous healing knowledge. Laboratory screening confirmed the presence of key secondary metabolites across all formulations, including flavonoids, tannins, alkaloids, phenolics, and terpenoids. Among the seven formulations tested, those based on Ziziphus mauritiana (bidara) and Annona muricata (soursop) showed the highest chemical diversity and antioxidant activity, with IC₅₀ values of 61.2 µg/mL and 74.5 µg/mL, respectively. These results support the pharmacological potential of traditional remedies and align with healer-reported uses related to immune function and disease prevention. Students reported significant educational gains, including improved understanding of phytochemistry, enhanced laboratory competence, critical thinking, and greater intercultural and ethical awareness. The Ethnomed-PjBL model demonstrated the capacity to embed scientific inquiry within culturally responsive frameworks, reinforcing the relevance of Indigenous knowledge in contemporary pharmaceutical education. By promoting equitable academic–community partnerships, this model contributes to broader efforts to decolonize health education and advance pharmaceutical sovereignty. It offers a replicable framework for integrating traditional knowledge into vocational health curricula, balancing scientific rigor with cultural respect. The study underscores the importance of ethical collaboration in preserving traditional knowledge systems while cultivating future health professionals who are both scientifically competent and culturally attuned.